NMR, HS‐SPME‐GC/MS, and HPLC/MSn Analyses of Phytoconstituents and Aroma Profile of Rosmarinus eriocalyx. Issue 10 (17th October 2017) - Bendif, Hamdi; Miara, Mohamed Djamel; Peron, Gregorio; Sut, Stefania; Dall'Acqua, Stefano; Flamini, Guido; Maggi, Filippo
Abstract : In this work, a comprehensive study on the chemical constituents of the aerial parts of Rosmarinus eriocalyx (Lamiaceae), an aromatic shrub traditionally consumed as a food and herbal remedy in Algeria, is presented. The aroma profile was analysed by headspace solid phase microextraction (HS‐SPME) coupled with gas chromatography‐mass spectrometry (GC/MS), whereas the crude extract constituents were analyzed by 1 H‐NMR and by high performance liquid chromatography coupled with mass spectrometry (HPLC/MS n ). Thirty‐nine volatile compounds, most of them being monoterpenes, have been identified, with camphor, camphene, and α ‐pinene as the most abundant constituents. 1 H‐NMR analysis revealed the presence of phenolic compounds and betulinic acid while HPLC/MS n allowed the identification of glycosilated and aglyconic flavonoids as well as phenylpropanoid derivatives. Some of these constituents, namely as betulinic acid, rosmanol, and cirsimaritin were reported for the first time in R .  eriocalyx . Abstract :